Respiratory Health Risks from H₂S Exposure at Indonesian Landfills: A Review of Key Individual and Exposure Related Risk Factors - Qolifah, Lina Nur; Suhartono; Nurjazuli (Griya Eka Sejahtera, 2025)
Background: Landfills emit various hazardous gases through the decomposition of waste, one of which is hydrogen sulfide (H₂S), a gas that is particularly harmful to the human respiratory system. Individuals living or working near landfills are at higher risk of developing respiratory disorders due to prolonged exposure to polluted air. This review aimed to identify the risk factors of H₂S exposure from landfills that contribute to respiratory problems.Methods: A literature review methodology was used by collecting studies from Google Scholar. Sixteen articles were selected based on predefined inclusion criteria after identification and screening.Results: The results of the review indicate that respiratory disorders are influenced by various factors, such as H2S concentration, H2S intake, H2S RQ value, exposure patterns (duration, frequency, and intensity), and individual characteristics (age, gender, nutritional status, use of personal protective equipment).Conclusion: The concentration of H2S is relatively low compared to other gases produced from TPA, and individual risk factors have an impact on lung function disorders.